The increasing importance of water management in the Dutch planning system - Frank Bruinsma; Mark Bokhorst (European Regional Science Association (ERSA), 2010)
In this paper the growing importance of water management, and thus the role of district water boards, in spatial planning is emphasized. First of all, due to the climate change rainfall will be more severe in relative short periods of time. Thus on the one hand the risk of flooding will increase, whereas on the other hand the periods of drought increase as well. This implies for the former situation that the water capacity of rivers must be increased and retention areas must be created. For periods of drought, large water reserves should be created. The rise of the sea level, due to the climate change, the descending of the northwestern part of the Netherlands in combination with long periods of draught causes a further inland penetration of salt seawater via the river deltas. A second cause of the increased importance of water management is that the polders in the western part of the country become too brackish by the endless pumping of fresh water out of the polder. Due to this constant pumping activity the salt seawater from deep in the underground rises up to the surface and causes problems for agricultural use of the polders. A final cause of the increased importance of water management is the transformation of the countryside from a single use agricultural production area into a multiple use consumption area where the public wants to recreate and enjoy nature. This implies that the level of the groundwater should vary according to the land use: from about 1 meter below surface in case of agricultural use to surface level in case of nature conservation in moorlands.
Keywords: 330